Peran Badan Pengawas Obat dan Makanan (BPOM) dalam Strategi Nasional Pengendalian Antimikroba Tahun 2025-2029 - Billa Nidia Hikmatiana; Patihul Husni (STIKES Columbia Asia Medan, 2025)
Antimicrobial resistance (AMR) is a major global threat, contributing to high mortality and infectious complications worldwide. In response, Indonesia has developed the National Strategy for the Control of Antimicrobial Resistance in the Health Sector for 2025–2029. Within this framework, the National Agency of Drug and Food Control (BPOM) plays a strategic role both as a lead organizer and partner in implementing cross-sectoral interventions. BPOM is involved in drafting regulations, supervising the distribution and use of antimicrobials, and conducting public education programs. Its role aligns with the people-centred and One Health approaches, emphasizing multi-sectoral collaboration and community engagement in AMR control. This study applies a normative legal approach based on literature and regulatory analysis to evaluate BPOM’s role in the national strategy.